Frequency and Microbiological Profile of Catheter-Related Infections in Hemodialysis Patients Receiving Gentamicin as Antimicrobial Lock Therapy for Prophylaxis - Mahmood, Sumbal Nasir; Asif, Sabaa; Anwar, Muhammad Amim; Naveed, Osama Kunwer (Pakistan Journal of Kidney Diseases, 2021)
Antibiotic lock solution (ALS) in the lumen of catheter is a mean to decrease the possibility of catheter related blood stream infection (CRBSI). We conducted this study using Gentamicin as ALS to observe the frequency of catheter related infections (CRI) including CRBSI and exit site infection in this hemodialysis patients being dialyzed through tunneled and temporary hemodialysis catheters. Methods This descriptive, cross sectional study was conducted at Dr. Ziauddin Hospital, North Campus between January 2017- December 2017. Symptomatic patients for CRBSI were included in this study. Blood culture from the catheter ports and periphery and exit site swab if pus visible were sent for culture sensitivity. Results Total 138 patients of either gender with age more than 18 years to less than 80 years were evaluated. 44.9% were male and mean age of patients was 58.79±14.05 years. 70.3% patients were diabetic for 15.61±4.61 years and 11.6% were using immunosuppressive drugs. The overall mean catheter duration was 22.27±14.39 days and mean hemodialysis duration was 25.32±44.31 weeks. Tunneled catheter was placed in 40.6% and 46.4% had femoral temporary catheters. Blood culture was done for 51 cases and 21.5% were positive. Tip culture was positive in 33.3% patients. In our study, 23.18% patients were found to have catheter related infections, out of which 61.5% were found with gentamicin resistance including colonization. Conclusion We report a high frequency of catheter related infections despite using ALS as prophylaxis, with predominant organisms being gram positives and a high incidence of gentamycin resistance.